Canine visceral leishmaniasis in area with recent Leishmania transmission: prevalence, diagnosis, and molecular identification of the infecting species - Josiane Valadão Lopes; Érika Monteiro Michalsky; Nathália Cristina Lima Pereira; Adão Junior Viana de Paula; Andreza Geisiane Maia Souza; Letícia Cavalari Pinheiro; Ana Cristina Vianna Mariano da Rocha Lima; Daniel Moreira de Avelar; João Carlos França-Silva; Virgínia Aguiar Sorice Lanzetta; Jarbas de Melo; Consuelo Latorre Fortes-Dias; et al. (Revista da Sociedade Brasileira de Medicina Tropical, 2020)
Abstract INTRODUCTION: Canine visceral leishmaniasis (CVL) is an endemic disease in Brazil, and integrated control actions have been adopted by the Brazilian Ministry of Health to control its spread. However, the transmission profile is unknown in areas with recent CVL cases, including Itaúna, located in the Brazilian state of Minas Gerais, where the present study was carried out. METHODS: A total of 2,302 dogs from 12 neighborhoods were serologically tested for canine VL using the current diagnostic protocol adopted by the Brazilian Ministry of Health. Test positivity rate (TPR) and CVL prevalence were determined for each neighborhood. The presence of Leishmania was assessed in 60 seropositive dogs which had been recommended for euthanasia. Twenty-two of them (37%) were asymptomatic, and 38 (63%) were symptomatic for CVL. Parasitological (myeloculture and smear/imprint) and molecular (PCR) methods were employed for Leishmania detection in bone marrow, spleen, mesenteric lymph nodes, and ear skin. The infecting Leishmania species was identified by DNA sequencing. RESULTS: CVL prevalence (per 1,000 dogs) varied from 0.0-166.67, depending on the neighborhood, with a mean of 68.96 (SD 51.38). Leishmania DNA was detected in at least one tissue from all seropositive dogs, with comparable TPR among tissues. Leishmania parasites were identified in most (54/60) seropositive dogs, and the infecting parasite was identified as Leishmania infantum in all of these. CONCLUSIONS: Prevalence of CVL is a contributor to the spread of visceral leishmaniasis in Itaúna.